2000
DOI: 10.1046/j.1432-1327.2000.01272.x
|View full text |Cite
|
Sign up to set email alerts
|

Fidelity analysis of HIV‐1 reverse transcriptase mutants with an altered amino‐acid sequence at residues Leu74, Glu89, Tyr115, Tyr183 and Met184

Abstract: Substitution of particular residues postulated to have a role in active site architecture can alter the overall fidelity of DNA polymerization by HIV-1. The effects of this kind of substitution were determined in a lacZ-based assay using HIV-1 reverse transcriptase with specifically mutated residues. We found that the reported higher fidelity of nucleotide incorporation by the Met1843Val and Glu893Gly mutant reverse transcriptases (RTs) was not reflected in a substantial increase in the overall fidelity for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 34 publications
2
29
0
1
Order By: Relevance
“…Part of this reorientation of the active site may be reflected in a change in the interaction between the amino acid at position 74 and the flipped out template base. This hypothesis is supported by a fidelity study that showed that RT L74V has an increased tendency to cause frameshift mutations (65). In a recent report, where similar resistance was observed to D4TTP by the V75T mutation, it was suggested that residues in the "template grip" region may interact with Gln 151 in a manner that can increase the selectivity of RT to nucleotide analogs (32).…”
Section: Role For the Hydrophobic Nature Of Cbvtp's Ribose Ring Inmentioning
confidence: 85%
“…Part of this reorientation of the active site may be reflected in a change in the interaction between the amino acid at position 74 and the flipped out template base. This hypothesis is supported by a fidelity study that showed that RT L74V has an increased tendency to cause frameshift mutations (65). In a recent report, where similar resistance was observed to D4TTP by the V75T mutation, it was suggested that residues in the "template grip" region may interact with Gln 151 in a manner that can increase the selectivity of RT to nucleotide analogs (32).…”
Section: Role For the Hydrophobic Nature Of Cbvtp's Ribose Ring Inmentioning
confidence: 85%
“…The average viral titer obtained with wild-type HIV-1 RT was 1.7 ϫ 10 4 CFU/50 ng of p24 CA. The n-fold decrease in mutation frequency represents an average change in mutation frequency for mutants obtained in in vitro or in vivo forward mutation assays using the lacZ alphapeptide reporter gene (8,16,17,31,39,40,59,67,77; reviewed in reference 72). The following symbols for RT genotypes were used: ϩ, wild type; F, Q151N; E, Q151M; s, M184I; ᮀ, M184V; OE, F116Y; ‚, F116W; , Y115F; ƒ, L74V; ࡗ, K65R; छ, E89G.…”
Section: Discussionmentioning
confidence: 99%
“…These differences could be due, in part, to the different mutation targets used. In this study, the entire lacZ gene was used as a mutation target, whereas in many of the cell-free fidelity studies, the lacZ␣ gene was used as a target (2,5,11,27,29,30,58,65). In cell-free systems, synthesis of one DNA strand is used to determine these rates.…”
Section: Discussionmentioning
confidence: 99%
“…The Q151N RT variant significantly decreased virus mutant frequencies while the K154A RT variant was not found to have a significant influence on virus mutant frequencies (Table 1). Intriguingly, another substitution in the dNTP binding site, Y115A, has been previously reported to decrease fidelity by a factor of 4 using the lacZ␣ gene (27). However, the Y115F and Y115V RT variants were found in lacZ␣ cell-free fidelity assays to have slightly lower error rates than that of wt RT (5).…”
Section: Analysis Of Hiv-1 Rt Single-amino-acid Variants On Virus Mutmentioning
confidence: 98%